New oral anticoagulants in atrial fibrillation and acute coronary syndromes: ESC Working Group on Thrombosis-Task Force on Anticoagulants in Heart Disease position paper. - De Caterina, R; Husted, S; Wallentin, L; Andreotti, F; Arnesen, H; Bachmann, F; Baigent, C; Huber, K; Jespersen, J; Kristensen, S; Lip, G; Morais, J; et al. (2012)
Until recently, vitamin K antagonists were the only available oral anticoagulants, but with numerous limitations that prompted the introduction of new oral anticoagulants targeting the single coagulation enzymes thrombin (dabigatran) or factor Xa (apixaban, rivaroxaban, and edoxaban) and given in fixed doses without coagulation monitoring. Here we review the pharmacology and the results of clinical trials with these new agents in stroke prevention in atrial fibrillation and secondary prevention after acute coronary syndromes, providing perspectives on their future incorporation into clinical practice. In phase III trials in atrial fibrillation, compared with warfarin, dabigatran etexilate 150 mg B.I.D. reduced the rates of stroke/systemic embolism without any difference in major bleeding; dabigatran etexilate 110 mg B.I.D. had similar efficacy with decreased bleeding; apixaban 5 mg B.I.D. reduced stroke, systemic embolism, and mortality as well as major bleeding; and rivaroxaban 20 mg Q.D. was noninferior to warfarin for stroke and systemic embolism without a difference in major bleeding. All these agents reduced intracranial hemorrhage. Edoxaban is currently being evaluated in a further large phase III trial. Apixaban and rivaroxaban were evaluated in phase III trials for prevention of recurrent ischemia in patients with acute coronary syndromes who were mostly receiving dual antiplatelet therapy, with conflicting results on efficacy but consistent results for increased major bleeding. Overall, the new oral anticoagulants are poised to replace vitamin K antagonists for many patients with atrial fibrillation and may have a role after acute coronary syndromes. Although convenient to administer and manage, they present challenges that need to be addressed.